Enhancing Global Teacher Performance Through Administrative Digitalization: Meningkatkan Kinerja Guru Global Melalui Digitalisasi Administrasi - Sambiono, Daris; Setiyono, Wisnu Panggah (Universitas Muhammadiyah Sidoarjo, 2024)
This study investigates the impact of management and administrative digitalization on teacher performance, moderated by work motivation, in three educational institutions within Perguruan Muhammadiyah Porong. Utilizing Partial Least Squares (PLS) regression analysis through SmartPLS 3.0 software, the research reveals that while digitalization of administration significantly enhances teacher performance, digitalization of management does not. Additionally, the interaction between digitalization and work motivation does not significantly influence performance. These findings emphasize the importance of administrative digitalization in improving teacher performance and suggest implications for educational institutions aiming to optimize digitalization strategies to enhance overall educational quality. Hightligh: Administrative digitalization improves teacher performance significantly. Work motivation's moderation on digitalization's impact is insignificant. Administrative digitalization crucial for enhancing overall educational quality. Keywords: Digitalization, Management, Administration, Teacher Performance, Work Motivation